Gut Microbiota Protected Against pseudomonas aeruginosa Pneumonia via Restoring Treg/Th17 Balance and Metabolism - Wen, Long; Shi, Lei; Kong, Xiang-Long; Li, Ke-Yu; Li, Hui; Jiang, Di-Xuan; Zhang, Fan; Zhou, Zhi-Guo (Frontiers in Cellular and Infection Microbiology, 2022)
Backgrounds and Purpose The theory of “entero-pulmonary axis” proves that pneumonia leads to gut microbiota disturbance and Treg/Th17 immune imbalance. This study is aimed to explore the potential mechanism of fecal microbiota transplantation (FMT) in the treatment of Pseudomonas aeruginosa pneumonia, in order to provide new insights into the treatment of pneumonia. Methods Pseudomonas aeruginosa and C57/BL6 mice were used to construct the acute pneumonia mouse model, and FMT was treated. Histopathological changes in lung and spleen were observed by HE staining. The expression of CD25, Foxp3 and IL-17 was observed by immunofluorescence. The proportion of Treg and Th17 cells was analyzed by flow cytometry. Serum IL-6, LPS, and IFN-γ levels were detected by ELISA. The expression of TNF-α, IFN-γ, IL-6, IL-2, Foxp3, IL-17, IL-10, and TGFβ1 in lung tissue homogenate was detected by qRT-PCR. 16S rRNA sequencing and non-targeted metabolomics were used to analyze gut microbiota and metabolism. Results Pseudomonas aeruginosa caused the decrease of body weight, food and water intake, lung tissue, and spleen injury in mice with pneumonia. Meanwhile, it caused lung tissue and serum inflammation, and Treg/Th17 cell imbalance in mice with pneumonia. Pseudomonas aeruginosa reduced the diversity and number of gut microbiota in pneumonia mice, resulting in metabolic disorders, superpathway of quinolone and alkylquinolone biosynthesis. It also led to the decrease of 2-heptyl-3-hydroxy-4(1H)-quinolone biosynthesis, and the enrichment of Amino sugar and nucleotide sugar metabolism. FMT with or without antibiotic intervention restored gut microbiota abundance and diversity, suppressed inflammation and tissue damage, and promoted an immunological balance of Treg/Th17 cells in mice with pneumonia. In addition, FMT inhibited the aerobactin biosynthesis, 4-hydroxyphenylacetate degradation, superpathway of lipopolysaccharide biosynthesis and L-arabinose degradation IV function of microbiota, and improved amino sugar and nucleotide sugar metabolism. Conclusions FMT restored the Treg/Th17 cells’ balance and improved inflammation and lung injury in mice with Pseudomonas aeruginosa pneumonia by regulating gut microbiota disturbance and metabolic disorder.